Viabilidade e ação de lectinas na germinação in vitro de grãos de pólen de dendezeiro (Elaeis Guineensis Jacq. – Arecaceae) - Sousa, Alexsandro dos Santos (2015)
In Brazil, research on Arecaceae pollen grains are related to melissopalynology, the palynotaxonomy, being scarce the physiology of pollen. Reproductive biology studies pollination are of great importance in different cultures, from their results can obtain parameters to be used to obtain a considerable increase in the production of croops, as well as the size and quality of fruits, helping for good economic income of the producers. In vitro pollen germination also allows you to check its viability and reproductive strength, and are important tools in breeding programs of plants, assisting in the selection of the most effective genotypes and training hybrids. The chapter one of this work consists of evaluation of the type of culture medium and implications on the choice of micronutrients which form part of its composition, as well as the pretreatment of specimens. It was observed that oil palm pollen (Elaeis guineensis Jacq.) Showed an increase in germination rates after being dissected for a period of four hours and the culture medium with only boric acid and calcium nitrate, in addition to the power source (sucrose) are efficient to display their germination potential. Chapter two contained in the evaluation glycoconjugate (lectins) on the pollen germination of oil palm, which was discussed metabolic interactions of these processes. Lectins are important regulators and operate in recognition and acknowledgment of pollen on the pistil and can act as genetic incompatibility factors. Germination was evaluated in BCa means (boron and calcium) with the addition of lectins: Crotalaria pallida lectin (CPL), Concanavalin A (ConA) and Jacalin (JAC) in two concentrations. An increase of the germination rate in the presence of ConA and CPL lectins and inhibition in the presence of JAC. The results of this study were valuable, since aggregate informative values and extend discussions on the processes involving the germination of pollen grains and formation of pollen tubes of oil palm.